Comparison of Transnasal Humidified Rapid-Insufflation Ventilatory Exchange and Facemasks in Preoxygenation: A Systematic Review and Meta-Analysis. (13th July 2022) - Li, Yongkai; Yang, Jianzhong
Abstract : Background . Transnasal Humidified Rapid-Insufflation Ventilatory Exchange (THRIVE) has received increasing attention and application as an effective noninvasive mode of ventilation in the treatment of clinical anesthesia and critically ill patients. The conclusions reached in clinical studies of THRIVE and facemask oxygenation are still controversial, and the main objective of this systematic review is to determine the advantages of THRIVE over facemask oxygenation in intensive care units, respiratory medicine, and perioperative preoxygenation. Methods . PubMed, Embase, Web of Science, and Cochrane Library have search restrictions. The search library was full of English language articles from the first publication to 15 July 2021. Eligible randomized controlled study designs were included. 245 records were screened, and 5 studies met the inclusion criteria, enrolling a total of 235 patients. Results . Studying the THRIVE group compared to the facemask group, three studies analyzing intubation time showed that there is no difference in the effect of THRIVE and facemasks (MD -1.22, 95% CI -7.23 to 4.78, and P = 0.69 > 0.05 ). Three studies analyzing apnea showed that there was no difference between the two groups (SMD 1, 95% CI -0.76 to 2.76, and P = 0.27 > 0.05 ). Three studies analyzing PaO2 after preoxygenation showed that THRIVE is more effective than facemasks (MD 72.58, 95% CI 31.25 to 113.90, Z = 3.44, and P < 0.001 ). Two studies analyzing oxygen saturation SpO2 after successful intubation showed that there was no difference in the effectiveness (MD 0.09, 95% CI -1.03 to 1.22, and P = 0.87 > 0.05 ). Two studies analyzing PCO2 after complete paralysis or intubation preoxygenation showed that there was no difference between the two groups (MD 2.76, 95% CI -1.74 to 7.26, and P = 0.23 > 0.05 ). Conclusions . THRIVE does not have a greater advantage over a facemask in improving apnea time, oxygenation time, PCO2, and SpO2, but it has an advantage in improving arterial partial pressure of oxygen (PaO2 ) after preoxygenation, which can improve PaO2 well. This trial is registered with the protocol registration number CRD42021268143 .